2018
DOI: 10.1002/osp4.149
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of weight loss in a 1‐year behavioural weight‐loss programme

Abstract: SummaryObjectiveIdentifying early predictors of weight loss is key for developing personalized treatment. However, few individual factors have been identified that predict weight loss during intervention, other than early weight loss itself.MethodsWomen with overweight or obesity (n = 186, mean ± SD age 50.0 ± 10.6 years, body mass index 34.0 ± 4.2 kg m−2) participated in the Portion‐Control Strategies Trial, a 1‐year randomized controlled weight‐loss trial with three intervention groups. Early changes in eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…In contrast, over 8 in 10 participants who did not respond early to treatment were unsuccessful in achieving 5% weight loss at 3 or 6 months. These findings illustrate the importance of early weight loss, which is consistent with past studies of behavioural interventions for weight loss . The GoalTracker trial is the first study to demonstrate this relation in the context of a standalone mHealth intervention, which holds promise as a less resource‐intensive and more scalable initial intervention strategy in stepped‐care approaches.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, over 8 in 10 participants who did not respond early to treatment were unsuccessful in achieving 5% weight loss at 3 or 6 months. These findings illustrate the importance of early weight loss, which is consistent with past studies of behavioural interventions for weight loss . The GoalTracker trial is the first study to demonstrate this relation in the context of a standalone mHealth intervention, which holds promise as a less resource‐intensive and more scalable initial intervention strategy in stepped‐care approaches.…”
Section: Discussionsupporting
confidence: 84%
“…those without a counselling component) (3)(4)(5). Early weight loss is a robust predictor of clinically meaningful weight loss (6)(7)(8) and has been used as a trigger in stepped-care behavioural interventions to implement rescue efforts for individuals not responding early to obesity treatment (6,(9)(10)(11). A 12-week internet-based weight loss study found a strong positive relation of early weight loss at 1 month predicting weight loss at 3, 6 and 12 months (12).…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial overlap between the variables recognized as key health lifestyle behaviours, that is dietary habits, physical activity, smoking, and drinking alcohol , and behaviours having a major impact on an individual's BMI, that is food choices and eating practices, physical activity, TV viewing, and sleep . Health lifestyle theories argue that focusing on a single or a small subset of behaviours does not sufficiently reflect the diversity of the social forces behind them .…”
Section: Introductionmentioning
confidence: 99%
“…Frequency of meals and having breakfast have both been inversely related to BMI . Time spent on food preparation might be indicative of the quality of diet as food prepared at home was shown to have a better nutritional profile than food eaten out of home . The quality of an individual's diet may also be affected by the duration of sleep , as sleep deprivation has been shown to be associated with food preferences, total energy intake, and metabolic processes .…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of these factors at baseline before the intervention could allow for tailored delivery of extra support for individuals who are less responsive to treatment (James et al, 2018).…”
Section: Introductionmentioning
confidence: 99%